Business Planning : Shining Star boutique / Nur Hanisah Othman ...[et al.] - Othman, Nur Hanisah; Ramli, Siti Nazurah; Mohd Razib, Rabiatul Adawiyah; Nasharuddin, Zaidah (2009)
Nowadays, people would like to involve in business. Such as, many people open business to get many experience and benefits . We also want to open business like boutique. Our company name is Shining Star plan to open on December 2009 which carries the label of Shining Star. Shining Star boutique would not be a reality without the support from various parties. Shining Star boutique is a label that is reliable when it comes to design with quality and versatility. Shining Star boutique believes in the motto Versatile, New, Conceptual, and Unique. The design of Shining Star are one of a kind, individual, and full of character. Shining Star boutique caters for all type of garments ranging from bridal gowns, casual denim wear, batik, uniform to menswear and others. In our boutique, we also prepare clothes for ladies. For ladies, we prepare suits, dresses, blouse, trousers, and skirt. We also make our design for our customer. Otherwise, we also accept customer opinion to make sure customer satisfied with their design. Our task was to come up with a solution for the readers in the form of illustrations or fashion sketches that interest and expensive. The factors that we choose this business because we have knowledge about how to make a design and how to create the clothes. At Shining Star we will give the best services that we can offer to make your dreams come true. Customer’s satisfaction means everything to us. Our commitment is to bring only the best for you at Shining Star boutique. The future prospects of the Shining Star realized that there is a huge potential in market for bridal couture. Thus, Shining Star boutique make an effort to diversify their creativity and business by creating tasteful exclusive designs with exquisite details fit for a queen especially for the brides to be .